The Effect of Locus of Control and Work Environment on Organizational Commitment and Organizational Citizenship Behavior at Regional Secretary Bintan - Rahmawati, Putri; Kawangung, Verlina Y; Husni, Faisal; Kurniadi, Didi (International Journal of Psychosocial Rehabilitation, 2026)
The development of human resources in the government environment is supporting the success of the implementation of government programs. The Regency Secretary and his staff assist the Regent in carrying out government, administrative, organizational and administrative arrangements as well as providing administrative services to all Bintan Regency Officials. In carrying out its duties and responsibilities, the Regency Secretariat has a lot of work done outside his duties and responsibilities outside of his job duties, but supports the smooth running of his work. In responding to this, high organizational citizenship behavior is needed for the executor of the task. This behavior is formed based on one’s self-control and the health of the work environment so that in the end, it will form a high work commitment to ultimately increase the person’s organizational citizenship. This research examines the direct and indirect effects of locus of control and work environment on organizational citizenship behavior both directly and through organizational commitment. The number of respondents in this study were 132 civil servants in Bintan Regency Secretariat. The method of analysis is done by path analysis with the help of SPSS. The study result indicates that the direct locus of control and work environment have a positive and significant effect on organizational commitment and organizational citizenship behavior. While the indirect effect also shows that locus of control influences organizational citizenship behavior through organizational commitment. The work environment influences organizational citizenship behavior through organizational commitment.